Cause-specific mortality among patients with renal cell carcinoma in the United States from 2000 to 2018 - Elgenidy, Anas; Awad, Ahmed K.; Cheema, Huzaifa Ahmad; Shahid, Abia; Kacimi, Salah Eddine Oussama; Aly, Mostafa Gaafa; Singla, Nirmish; Afifi, Ahmed M.; Patel, Hiten D. (Urologic oncology, 2023)
Objectives - There has been little focus on the non-cancer causes of death in patients with renal cell carcinoma (RCC). Therefore, we aimed to assess the frequency and risk of different causes of death, stratified by tumor stage, and demographics, after a diagnosis of RCC in the United States. - Materials and methods - Data on eligible patients with RCC from January 1, 2000, to December 31, 2018, in the United States were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Standardized mortality ratios for causes of death were calculated using the SEER*Stat software 8.3.9.2 for the overall population and stratified subgroups. - Results - A total of 165,969 patients with RCC were included and 60,290 (36.3%) died during follow-up. The majority of deaths were due to kidney cancer (51.3%) but a significant proportion was non-cancer causes (37.6%). The proportion of deaths attributed to RCC decreased with increasing follow-up with non-cancer causes becoming dominant after the fifth year following RCC diagnosis. Overall, cardiovascular diseases and cerebrovascular diseases were the most common non-RCC-related causes of death. AJCC stage I and localized RCC had the most deaths attributed to non-cancerous causes (66.2% and 61.2%, respectively) while AJCC stage IV and distant RCC had the most deaths due to RCC (86.2% and 86.5%, respectively). - Conclusion - A large proportion of RCC patients die of non-cancerous causes especially early-stage patients and advanced-stage patients who survive >5 years. Coordination of multidisciplinary care with relevant specialists depending on the stage of the disease is needed to better prevent death overtime from non-cancer causes.
Online verfügbar 22. Februar 2023, Artikelversion 12. April 2023
Gesehen am 06.07.2023